DREADD‐inactivation of dorsal CA1 pyramidal neurons in mice impairs retrieval of object and spatial memories. Issue 1 (5th December 2022) - Cinalli, David A.; Cohen, Sarah J.; Calubag, Mariah; Oz, Goksu; Zhou, Lylybell; Stackman, Robert W.
Abstract: The hippocampus, a medial temporal lobe brain region, is critical for the consolidation of information from short‐term memory into long‐term episodic memory and for spatial memory that enables navigation. Hippocampal damage in humans has been linked to amnesia and memory loss, characteristic of Alzheimer's disease and other dementias. Numerous studies indicate that the rodent hippocampus contributes significantly to long‐term memory for spatial and nonspatial information. For example, muscimol‐induced depression of CA1 neuronal activity in the dorsal hippocampus impairs the encoding, consolidation, and retrieval of nonspatial object memory in mice. Here, a chemogenetic designer receptor exclusively activated by designer drugs (DREADDs) approach was used to test the selective involvement of CA1 pyramidal neurons in memory retrieval for objects and for spatial location in a cohort of male C57BL/6J mice. Activation of the inhibitory (hM4Di) DREADDs receptor expressed in CA1 neurons significantly impaired the retrieval of object memory in the spontaneous object recognition task and of spatial memory in the Morris water maze. Silencing of CA1 neuronal activity in hM4Di‐expressing mice was confirmed by comparing Fos expression in vehicle‐ and clozapine‐ N ‐oxide‐treated mice after exploration of a novel environment. Histological analyses revealed that expression of the hM4Di receptor was limited to CA1 neurons of the dorsal hippocampus. These results suggest that a common subset of CA1 neurons (i.e., those expressing hM4Di receptors) in mouse hippocampus contributed to the retrieval of long‐term memory for nonspatial and spatial information. Our findings support the view that the contribution of the rodent hippocampus is like that of the primate hippocampus, specifically essential for global memory. Our results further validate mice as a suitable model system to study the neurobiological mechanisms of human episodic memory, but also in developing treatments and understanding the underlying causes of diseases affecting long‐term memory, such as Alzheimer's disease.